Pemanfaatan Sisa Baja Ringan Sebagai Pembuatan Alat Pembakar Ikan: Pembuatan Alat Pembakar Ikan - Herlinasari, Nasmi; Suteja, Suteja; Hidayatulah, Syarif; Sari, Nasmi Herlina; Sutaryono, Yusuf Akhyar (Jurusan Teknik Mesin FT Universitas Mataram, 2024)
Used light steel is used extensively in construction projects and is only provided to collectors at a reduced cost. It is derived from the leftover light steel building components. The goal of this project is to make a grill out of the leftover light steel parts that will withstand heat better and be more valuable than it was previously. The grill's shape facilitates easy heat absorption by the cooked material. This fish grill is made by first gathering leftover light steel, then bending and attaching the steel to form the grill using bolts. The activity's outcomes demonstrate that the grill made from leftover light steel is capable of producing consistent heat, allowing the fish to be cooked to perfection without being overly dry or scorched on the outside. Light steel additionally has an excellent level of heat resistance at high temperatures, extending the tool's service life and, eventually, raising UMKM's earnings.